Inhibitory effect of allicin and garlic extracts on the growth of cultured hyphae - Aala, Farzad; Yusuf, Umi Kalsom; Nulit, Rosimah; Rezaie, Sassan (Mashhad University of Medical Sciences, 2014)
Objective(s): Trichophyton rubrum (T. rubrum) is one of the most common dermatophytes worldwide. This fungus invaded skin appendages of humans and animals. Recently, resistance to antifungal drugs as well as appearance of side effects due to indication of these kinds of antibiotics has been reported. Besides, using some plant extracts have been indicated in herbal medicine as an alternative treatment of these fungal infections. The aim of this study was to investigate the effects of Garlic (Allium sativum) and pure allicin on the growth of hypha in T. rubrum using Electron miscroscopy. Materials and Methods: This study was carried out to observe the morphological changes of T. rubrum treated with allicin as well as aqueous garlic extract using scanning electron microscopy (SEM) and transmission electron microscopy (TEM). Results: SEM surveys, showed that hypha treated with allicin has rough and granular like surface, abnormal and irregularly-shape. However, hypha treated with garlic extract had rough and fluffy surface and also irregularly-shape. TEM studies also found that hypha treated with allicin displays disintegration of cytoplasm, breaking down in cell membrane and the cell wall, and collapsing of hypha, meanwhile hypha treated with garlic extract exhibiting degradation and dissolution of cytoplasm components, demolition of cell wall and cell membrane, and hypha appeared to break. Conclusion: The present study revealed that pure allicin (6.25 µg/ml and 12.5 µg/ml) is more efficient in inhibition of the growth in hyphal cells compare to the garlic extract (2 mg/ml and 4 mg/ml) and they could be used as alternatives in treatment of dermatophytosis.